2016
DOI: 10.1037/pspp0000072
|View full text |Cite
|
Sign up to set email alerts
|

Desired emotions across cultures: A value-based account.

Abstract: Values reflect how people want to experience the world; emotions reflect how people actually experience the world. Therefore, we propose that across cultures people desire emotions that are consistent with their values. Whereas prior research focused on the desirability of specific affective states or 1 or 2 target emotions, we offer a broader account of desired emotions. After reporting initial evidence for the potential causal effects of values on desired emotions in a preliminary study (N = 200), we tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(143 citation statements)
references
References 75 publications
3
122
0
7
Order By: Relevance
“…To assess participants' general preference for sadness (vs. happiness), we followed previous studies that assessed motivation to experience emotions (Kim et al, 2015;Tamir et al, 2016). Participants rated the degree to which they generally wanted to experience happiness and sadness in daily life (1 = not at all, 7 = extremely; e.g., "Please indicate the extent to which you generally want to feel happiness in your daily life").…”
Section: Instruments and Proceduresmentioning
confidence: 99%
“…To assess participants' general preference for sadness (vs. happiness), we followed previous studies that assessed motivation to experience emotions (Kim et al, 2015;Tamir et al, 2016). Participants rated the degree to which they generally wanted to experience happiness and sadness in daily life (1 = not at all, 7 = extremely; e.g., "Please indicate the extent to which you generally want to feel happiness in your daily life").…”
Section: Instruments and Proceduresmentioning
confidence: 99%
“…Although the mediating role of emotions in the relations between values and aggression has never been tested, theory suggests that values might activate specific emotions, and, indeed, evidence shows that values relate to specific emotions. For example, in a cross‐cultural study of adults, self‐enhancement values were related to a desire to feel anger (Tamir et al, ), and in a study of Finnish adolescents, guilt and empathy were correlated negatively with power values and associated positively with universalism and benevolence values (Silfver, Helkama, Lönnqvist, & Verkasalo, ).…”
Section: Mechanisms Underlying the Relations Between Values And Aggrementioning
confidence: 99%
“…Other recent research has examined the valuation of more complex emotional states; for instance, Tamir and colleagues [40] have demonstrated that across a variety of different national contexts, people want to feel the specific emotional states that are consistent with their values. For instance, the more people value self-transcendence (e.g., benevolence), the more they want to feel self-transcending emotions such as empathy and compassion.…”
Section: Valuation (And Devaluation) Of Other Emotional Statesmentioning
confidence: 99%